Sistem Transmisi Kontrol Mobil Robot dengan Menggunakan Gestur Tangan - Jati; Agung Samudra; Nanndo Yannuansa; Ahmad Fauzi (Elkom : Jurnal Elektronika dan Komputer, 2021)
The innovation of the robot cars today is moving very fast. The robot car is capable of being driven without using manual remote controls. One form of technological development in robot car control is by using hand gestures. The microcontrolle placed in the palm of the hand will read the direction of movement of our hands, then the instructions are transmitted to the robot car. The transmission system used in the microcontrolled circuit in the palm of the hand and the receiver circuit inside the robot car must be properly attached. This is influenced by the quality of programming language levels and the arduino mini pro and MPU-6050 circuits. Hand gesture directional readings are able to be easily readable and directly transmitted by the NRF24L01 module via radio waves. The response power of the robot car in receiving hand-move instructions can be received as far as 45 m. In addition to using a good arduino mini pro, the addition of antenna modules will also increase the quality and distance of the connection is getting farther..